2016
DOI: 10.4172/2472-1212.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital Mycoplasmosis and Pregnancy

Abstract: Urogenital mycoplasmas Ureaplasma urealyticum, Ureaplasma parvum and Mycoplasma hominis have long been considered commensals of human urogenital microflora. Several studies have recently clarified whether these bacteria could cause or be associated with various obstetric complications. Epidemiologic studies have found high prevalence of Ureaplasma spp. and M. hominis among otherwise healthy population. On the other hand, U. urealyticum, U. parvum and M. hominis have increasingly been linked to adverse pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Univariate, studies showed Mycoplasma genitalium (MG) infection to be significantly associated with cervicitis ( 22 ); however, these infections are least studied in the Indian context. Although it was reported that Mycoplasma hominis (MH), Ureaplasma urealyticum (UU) and Ureaplasma parvum (UP) are part of normal vaginal flora, but their serovars responsible for the obstetrics complications ( 23 ) tend to increase antimicrobial resistance ( 24 ). It has been reported that Ureaplasma species are observed more frequently in the symptomatic patients, whereas Mycoplasma species are observed in asymptomatic pregnant women ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Univariate, studies showed Mycoplasma genitalium (MG) infection to be significantly associated with cervicitis ( 22 ); however, these infections are least studied in the Indian context. Although it was reported that Mycoplasma hominis (MH), Ureaplasma urealyticum (UU) and Ureaplasma parvum (UP) are part of normal vaginal flora, but their serovars responsible for the obstetrics complications ( 23 ) tend to increase antimicrobial resistance ( 24 ). It has been reported that Ureaplasma species are observed more frequently in the symptomatic patients, whereas Mycoplasma species are observed in asymptomatic pregnant women ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about their effects in asymptomatic adolescents. These infections have been reported to contribute to infertility and adverse obstetric outcomes in symptomatic patients ( 23 , 33 ). Adolescent physiologies impel them toward high-risk infections though negligible data exists with respect to adolescent pregnancy ( 34 ).…”
Section: Introductionmentioning
confidence: 99%